Analisis Kemampuan Komunikasi Matematis Siswa kelas VII MTs Negeri 2 Kota Sungai Penuh pada materi segitiga dan segiempat - Verty Nur Amalia; Eline Yanty Putri Nasution; Diyah Hoiriyah (Venn: Journal of Sustainable Innovation on Education, Mathematics and Natural Sciences, 2022)
This study aims to determine students' communication skills. The research method used is qualitative. Qualitative research method is a research that is used to examine natural objects where the researcher is the key instrument. Data was collected through observation and analysis of student answer sheets. The results of this study were that students' communication skills were still low on triangles and quadrilaterals. This can be seen in the results of student answer sheets, teachers need to improve student abilities again. Qualitative research method is a research that is used to examine natural objects where the researcher is the key instrument.